Kebijakan Formulasi Sanksi Pidana Kerja Sosial terhadap Orang Membuang Sampah Dari Kendaraan di Kota Jambi - Reza Iswanto (Wajah Hukum, 2021)
Garbage is a problem in people's lives, especially in the people of Jambi city, so it is necessary to deal with waste related to the waste itself. For this reason, there should be a re-arrangement related to sanctions for people who dispose of waste from vehicles. When viewed from the problem, the research method is normative legal research with a statutory approach and a conceptual approach. The research materials are primary, secondary and tertiary legal materials with data collection techniques using documentary studies and qualitative analysis techniques. The regulation of fines for people throwing garbage from vehicles is regulated in Article 46 paragraph (3) letter c Jambi City Regional Regulation Number 5 of 2020 concerning Waste Management. Then the implication of social work criminal sanctions for people throwing garbage from vehicles, namely providing a deterrent effect as well as giving lessons to perpetrators and the policy of formulating social work criminal sanctions for the future is that social work criminal sanctions should be applied in Jambi City Regional Regulation Number 5 of 2020 concerning Management Garbage because it is an effort to overcome so that in the future there will be no more people in the city of Jambi who throw garbage from their vehicles.